OSMOTIC RESPONSES OF SEGARA ANAKAN FINE SHRIMP (Metapenaeus elegans) ADULTS IN VARIOUS SALINITY AND MOLTING STAGES - Sutrisno Anggoro; S ubandiyono (JOURNAL OF COASTAL DEVELOPMENT, 2012)
A research on eco-physiological characteristics of fine shrimp (Metapenaeus elegans) with special emphasis on the osmotic responses and isosmotic medium requirement for adult spawners in various molting stages was conducted. Adult stocks of M. elegans origin from the Segara Anakan lagunas of the South West of Central Java region were collected and used as experimental shrimps. The shrimps were hold in three 500 l-acclimation tanks and treated according to Anggoro and Nakamura’s method. The seawater salinity level in the tank 1, 2, and 3 was 25, 28, and 22 ppt, respectively. Osmotic response of the shrimps was examined during 3 molting stages, i.e. pre-molt/ post-molt, molt, and inter-molt phases by using an automatic microosmometer Roebling. The results showed that osmotic responses were closely related to the salinity of water medium and molting stages. It was also found that the minimum osmotic works of fine shrimp occurred in isosmotic medium, i.e. 16 to 20 ppt for post-molt, 28 to 30 ppt for molt, and 22 to 25 ppt for inter-molt stages. It was concluded that the range of isosmotic media for the adult of fine shrimp was 22 to 28 ppt or equals to 642.06 to 817.31 mOsm/l H2O.